Mechanisms of antibacterial immunity of mucous membranes - Franĕk, J; Libich, J; Kubín, V (Folia microbiologica, 1984)
A survey based on both literary data and the authors own results, concerning the mechanisms of sIgA-mediated antibacterial immunity, is presented. Secretory IgA is characterized as a specific component of the immune system of mucous membranes, which can recognize harmful bacterial and distinguish them from indigenous microflora physiologically colonizing the mucous membranes, to fix them to the mucous membrane surface and to direct further factors, such as mucin, lysozyme, etc. (which form the effector component of the mucous membrane immunity system) for their final inactivation and neutralization.
Keywords: fyziologie bakterií; Immunoglobulin A, Secretory; Humans; Mucous Membrane; aerosoly; protilátky bakteriální; Bacterial Vaccines; nosní sliznice; lidé; zvířata; myši; Aerosols; Nasal Mucosa; Saliva; bakteriální vakcíny; Mice; Antibodies, Bacterial; ústní sliznice; sliny; imunoglobulin A sekreční; sliznice; Mouth Mucosa; Animals; Bacterial Physiological Phenomena